Risk Factors for Trauma-Induced Coagulopathy- and Transfusion-Associated Multiple Organ Failure in Severely Injured Trauma Patients - Balvers, Kirsten; Wirtz, Mathijs R.; van Dieren, Susan; Goslings, J. Carel; Juffermans, Nicole P. (Frontiers in Medicine, 2015)
Background: Both trauma-induced coagulopathy (TIC) as well as transfusion strategies influence early outcome in hemorrhagic trauma patients. Their impact on late outcome is less well characterized. This study systematically reviews risk factors for TIC- and transfusion-associated multiple organ failure (MOF) in severely injured trauma patients. Material and methods: A systematic search was conducted in PubMed and Embase. Studies published from 1986 to 2013 on adult trauma patients with an Injury Severity Score (ISS) ≥16, investigating TIC or transfusion strategies with MOF as primary or secondary outcome, were eligible for inclusion. Results of the included studies were evaluated with meta-analyses of pooled data. Results: In total 50 studies were included with a total sample size of 63,586 patients. Due to heterogeneity of the study populations and outcome measures, results from 7 studies allowed for pooling of data. Risk factors for TIC-associated MOF were hypocoagulopathy, hemorrhagic shock, activated protein C, increased histone levels and increased levels of markers of fibrinolysis on admission. After at least 24 hours after admission, the occurrence of thromboembolic events was associated with MOF. Risk factors for transfusion-associated MOF were the administration of fluids and red blood cell units within 24 hours post-injury, the age of red blood cells (>14 days) and a ratio of FFP:RBC ≥1:1 (OR 1.11, 95% CI 1.04-1.19). Conclusion: Risk factors for TIC-associated MOF in severely injured trauma patients are early hypocoagulopathy and hemorrhagic shock, while a hypercoagulable state with the occurrence of thromboembolic events later in the course of trauma predisposes to MOF. Risk factors for transfusion-associated MOF include administration of crystalloids and red blood cells and a prolonged storage time of red blood cells. Future prospective studies investigating TIC- and transfusion- associated risk factors on late outcome are required.